Introduction of a new parameter 'Mastoid to Gonion Height' and its comparative evaluation with established pa cephalometric parameters in sex determination: An analytical study - Ramhari Sathawane; Samiksha Tripathi; Vidyarjan Sukhadeve (Wolters Kluwer Medknow Publications, 2022)
Introduction: Skeletal remains have a vital role in the differentiation of sex in forensic studies. Skull is the second most sexed skeleton after the pelvis. PA cephalogram is more precise and provides numerous anatomic points and planes in the frontal profile for comparison. Aim: To introduce a new parameter 'Mastoid to Gonion height,' and compare its accuracy with established PA cephalometric parameters in sex determination using discriminant functions. Materials and Methods: A hundred males and females each aged 25 to 60 years were included. A total of eight planes were constructed on PA cephalograms and measured. The data were analyzed using discriminant analysis. Results: The linear measurements were found greater in males than females. Among the studied parameters, Bizygomatic width and Mastoid to Gonion height had a high sex discriminating ability. The discriminant function (DF) equation correctly predicted the gender in 88.5% of subjects. Conclusion: The new parameter "Mastoid to Gonion" height has been successfully introduced. It is found to be the second-best strong predictor parameter and can be used singly for sex determination. The parameter Bi-zygomatic width also contributed most significantly and can be used singly. The DF equation is proposed to predict new cases.